Piloting the multi-family approach in community-based rehabilitation: an observational and interview-based study. (August 2017) - Mitwalli, Suzan; Rabaia, Yoke
Abstract: Background: In Palestine, as in many societies, children with a physical or mental disability and their families often experience stress related to stigma and isolation. Over the course of one year, the community-based rehabilitation programme in the north of the West Bank pioneered a multi-family group approach, originally developed in the UK, to facilitate six support groups for a total of approximately 50 mothers of children with a disability. The method is based on the premise that people who share similar situations can provide company, stress relief, and practical problem-solving ideas to each other. Methods: We conducted intervention research into the implementation and adaptation of the multi-family group approach to the local context. This research included systematic participatory observation of group sessions, reflection meetings, and training workshops, and informal interviews with 12 community-based rehabilitation workers and supervisors throughout the process of design of the project, initial specialist training of community health workers, and on-the-job mentoring. We conducted systematic comparative analysis of all observation notes and informal interviews. We obtained ethics approval and informed consent. Findings: Community-based rehabilitation teams gradually gained confidence in co-facilitating groups using the multi-family group approach techniques. The sessions combined enjoyment and relaxation with serious discussions over shared personal, family, and community experiences, and provided the participants with new ways for seeking and offering support. Over time, observations in sessions and interviews with mothers and group facilitators suggested that social isolation among group members diminished and mothers became more active in the group and the wider community. Interpretation: The multi-family group approach has meant that the group participants are no longer merely programme beneficiaries but have become active participants in the psychosocial component of community-based rehabilitation. Although in the West this approach is mostly implemented by specialists, our study shows that with intensive training and on-the-job mentoring, community health workers can successfully adapt the method to develop social support networks for mothers of children with a disability in Palestinian and possibly other non-Western settings. Funding: War Trauma Foundation (Netherlands).